Zoneamento das áreas de risco a inundação da área urbana de Itaqui-RS - Saueressig, Silene Raquel (2012)
The aim of this study is to establish the location of the urban areas with risk of flood in Itaqui/RS, located at the edges of the Uruguai River in Western RS. To achieve this goal a data base of flooding was organized with all the floods that occurred between the years 1980 to 2010. It was identified the part of the urban area susceptible to flooding by determining the level of hazard and the different aspects of vulnerability through the characteristic of occupations; finally from the correlation between the aspect of hazard and vulnerability, was determined the aspect of risk in the affected areas. The methodological procedures involved four steps: Theoretical base and data collection, analysis of natural and social conditions of the disaster, preparation of fundamental maps of hazard and vulnerability; and analysis of results, zoning and preparation of the risk map. The materials used were topographic map, satellite images, GPS, hydrological data and documents. With the results it was possible to estimate two levels of hazard, one related to recurrent floods that have defined areas of high hazard, and the other related to the extraordinary flood of 1983, which delimited the area of low hazard. The vulnerability has been established in three aspects from the constructive pattern of houses and public infrastructure. To sum up, it was possible to estimate four levels of risk from the correlation of the data. The results of this work may well help other research papers and allow planning proposals and planning urban infrastructure of Itagui-RS. Key words: Flood, Urban area, Zoning, Risk